E-commerce and household consumption in the United States: An arrangement of convenience - Lloyd George Banda; Zahra Zahir Kassam (Cogent Business & Management, 2023)
E-commerce is a comparatively classical concept that emerged into the business language in the 1970s. However, the theoretical and empirical conceptualization of the concept in marketing or consumer behaviour and economics is scanty. Therefore, we seek to statistically examine the impact of marketing strategies measured by the E-commerce index on household consumption in the United States (U.S.). Thus, the study used annual time series for data from 1990 to 2021. The study employed the autoregressive distributed lag approach, bounds cointegration, and the error correction model to establish the long-run relationship among the variables. Empirical findings revealed a positive relationship between e-commerce marketing and real household consumption in the U.S. For example, a one-unit improvement in e-commerce marketing results in a 0.72 per cent point increase in real household consumption in the long run. Unemployment also depicted a rare positive relationship, and we attributed the phenomenon to consumer confidence in the economy. Furthermore, the results showed that inflation negatively influences real household consumption in the U.S. in the long run. The study validates Engel, Kollat, and Blackwell's model in the United States, through which we argue that the better the information firms feed consumers, the higher the household consumption and the more the sales revenue and profitability a firm earns.
Keywords: 650; ARDL; consumption; E-commerce; EKB Model; inflation; marketing; unemployment